Pelatihan Copy Writing dan Desain Poster Digital dalam Mendukung Program Kampung KB Desa Sanggrahan - Vemas Nurreza Pradana; Stefven Chandra Widjaya; ⁠Aji Bagus Pamungkas; Salsabila Nur Halisa; ⁠Nining Masruroh; Lessika Dita Oktaviani; Popi Andiyansari (Universitas Teknologi Yogyakarta, 2025)
Digital poster design and copywriting training has an important role in supporting the KB Village program in Prambanan District, one of which is Sanggrahan Village. This activity aims to improve the skills of KB Village cadre women in creating effective communication media using the Canva application. The activity method includes seminars, practical training, and evaluation sessions through pre-test and post-test. The evaluation results showed an increase in participants' understanding of copywriting and digital poster design, with an increase in understanding scores of 25.3% for copywriting and 30.3% for poster design. This training provides benefits in improving the digital literacy of KB Village cadres as well as the effectiveness of disseminating information on family planning programs. The success of this activity is expected to become a model for technology-based community empowerment in other areas.